PEMANFAATAN SARANA DAN PRASARANA TERHADAP PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN DI MI AL-ISLAM GIWANGAN YOGYAKARTA - Rafi Pradipa; Aprilia Nurulita; Sedya Santosa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is grounded in the challenges related to the suboptimal utilization of facilities and infrastructure in supporting students’ Qur’anic reading skills at MI Al-Islam Giwangan, Yogyakarta. Limitations such as inadequate Qur’anic mushafs, insufficient learning media, and the underuse of educational technology hinder the effectiveness of Tahfiz and tartil learning activities. These issues reduce students’ learning enthusiasm, restrict innovation, and prevent the creation of a conducive Qur’anic learning environment. Therefore, this study aims to: (1) analyze the actual condition and optimization of facilities and infrastructure used to support Qur’anic learning; and (2) examine the impact of their utilization on improving students’ Qur’anic reading and memorization abilities. This research employs a descriptive qualitative approach, with primary data obtained through observations, interviews, and documentation, while secondary data include books, journals, and institutional documents. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that MI Al-Islam Giwangan has utilized facilities such as the school mosque, improved classrooms under the MLB BAZNAS program, internet access, electricity, mushafs, whiteboards, and audiovisual media to support Qur’anic learning. Effective use of these facilities combined with teachers’ guidance has resulted in positive impacts, including increased reading fluency, improved tajweed accuracy, enhanced motivation, and the development of a Qur’anic literacy culture within the school environment. However, the research also identifies several obstacles, including limited classroom capacity, varying students’ initial abilities, and restricted funding for infrastructure development. Overall, the study concludes that facilities and infrastructure significantly contribute to the effectiveness of the Tahfiz Al-Qur’an program at MI Al-Islam Giwangan.